Runaway jury [videorecording (DVD)] - Fleder, Gary; Cusack, John, 1966-; Hackman, Gene; Hoffman, Dustin, 1937-; Grisham, John (20th Century Fox Home Entertainment, 2004)
After a man dies in a shooting incident, his wife files a lawsuit against the company that manufactured the gun. Her lawyer argues that the firm in question knew the shop which sold the weapon was not following federal regulations. As the case goes to trial, the firearm manufacturer takes no chances on the outcome, and they hire Rankin Fitch, a "jury consultant" who makes it his business to see that he knows enough about the jurors to be able to guarantee the result of the trial.